Cultural Asymmetry as a Problem in the Dutch-language Translations of Popiół i diament, Mała apokalipsa and Dukla - Tryczyńska, Katarzyna (Werkwinkel, 2016)
Culture is present in texts created in a certain literary system and socio-cultural context on every level and becomes particularly visible in culture-specific items (CSIs). They anchor the texts into a certain culture and as such pose serious translation problems. At the same time culture is embedded in the system of transnational relations where there is always cultural asymmetry that exerts influence on the translation process. The position of the culture and the language in the international system tends to be reflected in translator’s choices. This paper addresses the issue of the cultural asymmetry and culturebound translation problems in the Dutch translations of modern Polish literature. For this purpose the author takes a close look at the translations of Popioł i diament [Ashes and Diamonds], Mała apokalipsa [A minor apocalypse] and Dukla [Dukla].